2008
DOI: 10.1111/j.1464-410x.2008.07611.x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of the pathological T2 subclassification for prostate cancer in the 2002 Tumour‐Nodes‐Metastasis staging system

Abstract: OBJECTIVE To evaluate the prognostic role of the 2002 Tumour‐Nodes‐Metastasis (TNM) pT2 subclassification for biochemical recurrence (BCR) after radical prostatectomy (RP) for prostate cancer. PATIENTS AND METHODS The 1997 TNM staging system is based on one subdivision for organ‐confined prostate tumours (T2a, unilateral; T2b, bilateral involvement). The 2002 TNM staging system subdivides unilateral involvement into T2a (half of one lobe or less) and T2b (more than one half of one lobe), while bilateral involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
3
12
0
1
Order By: Relevance
“…In contrast, patients with a biopsy positive for cancer, but with no cancer in the radical prostatectomy specimen, have no increased risk of tumor recurrence or progression. 50,[56][57][58][59] European urologists have suggested that in these cases, pT2 could be further characterized as pT2(À), where (À) indicates that cancer was not detected in the surgical specimen. Another alternative is to grade these tumors as pT2 ( þ bx/Àrp) to indicate the special situation of a positive biopsy ( þ bx) with no cancer detected in the radical prostatectomy specimen (Àrp).…”
Section: Radical Prostatectomy Specimens With No Carcinoma On Initialmentioning
confidence: 99%
“…In contrast, patients with a biopsy positive for cancer, but with no cancer in the radical prostatectomy specimen, have no increased risk of tumor recurrence or progression. 50,[56][57][58][59] European urologists have suggested that in these cases, pT2 could be further characterized as pT2(À), where (À) indicates that cancer was not detected in the surgical specimen. Another alternative is to grade these tumors as pT2 ( þ bx/Àrp) to indicate the special situation of a positive biopsy ( þ bx) with no cancer detected in the radical prostatectomy specimen (Àrp).…”
Section: Radical Prostatectomy Specimens With No Carcinoma On Initialmentioning
confidence: 99%
“…Although clinical prostate cancer (PCa) T2 sub‐stage evaluation appears to be a useful independent predictor of biochemical disease‐free survival (bDFS) [1], there is growing evidence that pathological T2 sub‐staging does not have the same value [2–8]. After its introduction in 1992, the American Joint Committee on Cancer/International Union Against Cancer (AJCC/UICC) tumour, node, metastases system became the standard method in which PCa is clinically and pathologically staged [9].…”
Section: Introductionmentioning
confidence: 99%
“…Biyokimyasal nüksü öngörmede T2 alt sınıflamasının katkısının değerlendirildiği başka bir çalışmada, ameliyat öncesi PSA ve patolojik Gleason skorunun 7 ve 8-10 olması biyokimyasal nüks bakımından öngörücü iken, patolojik T2 alt gruplarının herhangi bir katkısının olmadığı bulunmuştur. [19] 2002 TNM sınıflamasına göre pT2b tümörlerin saptanma oranı çalışmaların çoğunda çok düşüktür, [20][21][22] hatta bazı çalışmalarda hiç saptanmamıştır. [14] Farklı olarak bir çalışmada prostata sınırlı tümörlerin %61.1'inin pT2b olduğu bulunmuştur.…”
Section: Discussionunclassified